Ecological Control of Fecal Indicator Bacteria in an Urban Stream - Surbeck, Cristiane Q; Jiang, Sunny C; Grant, Stanley B (Environmental science & technology, 2010)
Fecal indicator bacteria (FIB) have long been used as a marker of fecal pollution in surface waters subject to point source and non-point source discharges of treated or untreated human waste. In this paper, we set out to determine the source(s) of elevated FIB concentrations in Cucamonga Creek, a concrete-lined urban stream in southern California. Flow in the creek consists primarily of treated and disinfected wastewater effluent, mixed with relatively smaller but variable flow of runoff from the surrounding urban landscape. Dry and wet weather runoff contributes nearly 100% of FIB loading to Cucamonga Creek, while treated wastewater contributes significant loading of nutrients, including dissolved organic carbon (DOC), phosphorus, nitrate, and ammonium. FIB concentrations are strongly positively correlated with DOC concentration in runoff (Spearman’s ρ ≥ 0.66, P ≤ 0.037), and microcosm studies reveal that the survival of Escherichia coli and enterococci bacteria in runoff is strongly dependent on the concentration of both DOC and phosphorus. Below threshold concentrations of 7 and 0.07 mg/L, respectively, FIB die off exponentially (die-off rate 0.09 h−1). Above these thresholds, FIB either grow exponentially (growth rate 0.3 h−1) or exhibit a periodic steady-state in which bacterial concentrations fluctuate around some mean value. The periodic steady-state pattern is consistent with a Lotka−Volterra predator−prey oscillation model, and the clearance rate (20 μL predator−1 h−1) obtained by fitting the model to our data is consistent with the hypothesis that predacious protozoa regulate FIB concentrations in runoff at high DOC concentrations. Collectively, these results indicate that FIB impairment of Cucamonga Creek is best viewed as an ecological phenomenon characterized by both bottom-up and top-down control.